Ribosomal Protein RPL10A Contributes to Early Plant Development and Abscisic Acid-Dependent Responses in Arabidopsis - Ramos, Rocío Soledad; Casati, Paula; Spampinato, Claudia Patricia; Falcone Ferreyra, María Lorena (Frontiers in Plant Science, 2020)
Plant ribosomal proteins play universal roles in translation, although they are also involved in developmental processes and hormone signaling pathways. Among Arabidopsis RPL10 family members, RPL10A exhibits the highest expression during germination and early development, suggesting that RPL10A is the main contributor to these processes. In this work, we first analyzed RPL10A expression pattern in Arabidopsis thaliana using transgenic RPL10Apro:GUS plants. The gene exhibits a ubiquitous expression pattern throughout the plant, but it is most strongly expressed in undifferentiated tissues. Interestingly, gene expression was also detected in stomatal cells. We then examined protein function during seedling establishment and abscisic acid (ABA) response. Heterozygous rpl10A mutant plants show decreased ABA-sensitivity during seed germination, are impaired in early seedling and root development, and exhibit reduced ABA-inhibition of stomatal aperture under light conditions. Overexpression of RPL10A does not affect the germination and seedling growth, but RPL10A-overexpressing lines are more sensitive to ABA during early plant development and exhibit higher stomatal closure under light condition both with and without ABA treatment than wild type plants. Interestingly, RPL10A expression is induced by ABA. Together, we conclude that RPL10A could act as a positive regulator for ABA-dependent responses in Arabidopsis plants.